Tracheal Tissue Engineering: Principles and State of the Art - Marco Mammana; Alessandro Bonis; Vincenzo Verzeletti; Andrea Dell’Amore; Federico Rea (Bioengineering, 2024)
Patients affected by long-segment tracheal defects or stenoses represent an unsolved surgical issue, since they cannot be treated with the conventional surgery of tracheal resection and consequent anastomosis. Hence, different strategies for tracheal replacement have been proposed (synthetic materials, aortic allografts, transplantation, autologous tissue composites, and tissue engineering), each with advantages and drawbacks. Tracheal tissue engineering, on the other hand, aims at recreating a fully functional tracheal substitute, without the need for the patient to receive lifelong immunosuppression or endotracheal stents. Tissue engineering approaches involve the use of a scaffold, stem cells, and humoral signals. This paper reviews the main aspects of tracheal TE, starting from the choice of the scaffold to the type of stem cells that can be used to seed the scaffold, the methods for their culture and expansion, the issue of graft revascularization at the moment of in vivo implantation, and experimental models of tracheal research. Moreover, a critical insight on the state of the art of tracheal tissue engineering is also presented.